Comparative Study on Organic Calcium Diffusion and Content in Apples and their Influence on Anna Apple Fruits Quality (Global Journal of Science Frontier Research, 2023)
This study was conducted during the two successive seasons 2021 and 2022 using Anna apples The trees were sprayed by using some organic calcium solution to compare their efficacy on providing the skin and flesh tissues with calcium which reflects on the fruit quality The trees were sprayed twice at the rapid elongation and maturity stages in both seasons treatments included tap water as the control calcium lignosulfonate at 0 2 and at 0 4 calcium foliate at 0 2 and at 0 4 calcium acetate at 1 calcium acetate at 1 plus urea at 1 and calcium acetate at 1 plus ethanol at 2 The non-ionic surfactant top film at 0 05 v v was added to all treatments to reduce the surface tension and to increase the contact angle Treatments resulted in increasing calcium content in the skin and the flesh of Anna apples the highest magnitude of increase was obtained in the skins and flesh of calcium acetate treated fruits plus ethanol as well as in the flesh Calcium acetate plus urea was also effective on increasing calcium content in both tissues of apple fruit The application of calcium lignosulfonate at 0 4 also resulted in a significant increase in calcium content of the skin and the flesh Calcium foliate was the least effective organic calcium compound than other forms but was also effective on increasing calcium content in apple tissues Fruit quality was also affected as a result of the variations of the diffused organic calcium Thus use of organic calcium is feasible and beneficial since calcium can translocate in a soluble form with the plant tissues
Keywords: organic calcium; calcium lignosulfonate; calcium acetate; calcium foliate; calcium content; apple quality